2021
DOI: 10.3991/ijet.v16i01.18227
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Study of Multimedia and Virtual Technology in Art Education

Abstract: Art education an important part of aesthetic education. It is indispensable for the comprehensive and healthy development of human beings. The basic task is to cultivate creative ability, human aesthetics, and apprec iation. Art education is conducive to improving the humanistic cultivation of young students, enhancing the spiritual realm of human beings, and cultivating the creative ability of young people. It has irreplaceable social, cultural, and an-thropological significance for promoting the comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 3 publications
0
18
0
2
Order By: Relevance
“…Although few studies have directly investigated the relationship between participation in interest classes and cognitive ability, some studies showed the positive influences of long-term art education such as painting, music and dance on cognitive abilities ( 31 , 32 ). For example, Liu et al ( 33 ) argued that art education could cultivate students’ physical functions, observation, imagination, creativity, and “healthy” personality.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have directly investigated the relationship between participation in interest classes and cognitive ability, some studies showed the positive influences of long-term art education such as painting, music and dance on cognitive abilities ( 31 , 32 ). For example, Liu et al ( 33 ) argued that art education could cultivate students’ physical functions, observation, imagination, creativity, and “healthy” personality.…”
Section: Introductionmentioning
confidence: 99%
“…An example of interactive multimedia is a learning presentation that allows the users to choose which topic they want to study without waiting for the complete presentation to be broadcast [60]. The interactive multimedia using the basics of animation is developed based on the demands in the field [34,60]. The materials of the subject will be difficult to understand if they are not accompanied by visualization, which eventually affects the low learning outcomes of students [30].…”
Section: 2mentioning
confidence: 99%
“…Learning center is composed of two parts: teaching tools and rich media. The virtual teaching and learning tools are mainly to digitize the traditional paper textbooks [14][15][16][17][18][19], and the rich media are sub-divided into four parts: images, texts, audios, and videos. With the help of this module, the teaching contents can be displayed for students in the forms of images, texts, audios, and videos more vividly, and it can enrich students' audiovisual experience, and inspire their interest; at the same time, this part can create virtual scenes that seamlessly connect the real scenes so that the teaching activities can be carried out in the corresponding teaching scenes to improve the teaching efficiency.…”
Section: Electronic Textbooksmentioning
confidence: 99%